THU0042 in vivo pro-inflammatory and anti-inflammatory cytokines levels in patients with rheumatoid arthritis. (1st June 2001) - Fong, KY; Yoon, KH; Koh, DR; Sivalingam, PS; Ng, SC
Abstract : Background: Pro-inflammatory and anti-inflammatory cytokines play important roles in the rheumatoid activity process. Objectives: This study aims to demonstrate the cytokine profiles in rheumatoid arthritis (RA) patients with active and inactive disease process. Methods: Fifty-three Chinese rheumatoid arthritis patients (8M:45F) and 38 healthy individuals (19M:19F) were enrolled into the study. RA patients were classified as having active disease or in remission according to clinical and serological criteria (morning stiffness, joint pain, joint tenderness, joint swelling, ESR, CRP). At venepuncture, the patients and healthy controls did not have any active infective process. All except 3 patients (in remission) were on SAARDs. Sera obtained in the morning were assayed for the following cytokines: TNFa, IFNg, TGFb, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12 and for rheumatoid factor (RF) by the ELISA method. HLA-DRB1*04 typing was performed using PCR-RFLP. Results: Forty-two patients had active disease and 11 patients were in remission. Rheumatoid factor was detected in 28 patients and HLA-DR*0405 allele was significantly elevated in RA patients (p < 0.001). TNFa, IL-6 and IL-8 were significantly elevated in RA patients when compared to controls (p < 0.01, p < 0.001, p < 0.018, respectively). Patients with RF positivity were noted to have much higher levels of these 3 pro-inflammatory cytokines. There was however no association with HLA-DR*0405. The anti-inflammatory TGFb was noted to be significantly lower in active patients when compared to inactive patients or controls (p < 0.05). Conclusion: In conclusion, the serum pro-inflammatory cytokines were significantly elevated in RA patients irrespective of their clinical disease activity while serum TGFb was significantly depressed in active RA patients and normalises when in remission. The exact role that TGFb plays in RA is yet to be fully elucidated.